The 'Big Bang' theory reconsidered: Some thoughts on the fabric of early Ghanaian history - (:unkn) unknown (My University, 2012)
Paper presented at the 50th Anniversary Conference, Centre of African Studies, University of Edinburgh, 6-8 June 2012; Panel on 'Recent Research in the Early Modern History of Atlantic Africa'
Keywords: African Research